Islamic Philanthropy Employee Work Values (Case Study Lasizmu Branch Office) - Moh. Alfiyan Lu’lu Firdaus (Faculty of Economics and Management, 2023)
This study uses a qualitative method to analyse the work values of the Lazismu Service Office employees (Lembaga Amil Zakat Infak Sadaqoh Muhammadiyah) located in Adiwerna District. The results of the interview show that the spiritual motivation aspect of work has the most influence on the work value of employees. It can be seen that there is a spiritual side that employees feel and experience while working. This has an impact on employee attitudes and behaviour.